Analisis Tingkat Pengetahuan Mahasiswa Program Studi Kedokteran Universitas Tanjungpura terhadap Penggunaan Obat Generik - Milenia Kamban; Ressi Susanti; Nurmainah Nurmainah (Universitas Batanghari Jambi, 2022)
Generic drugs are known to contain the same ingrediants as patent/branded drugs. So far, many people still have the view that generic drugs are drugs with low quality. The purpose of this study was to describe the percentage and compare the level of knowledge of students in the medical study program at Tanjungpura University. The method used is an observational method using an online in the form of a google form research design cross sectional an analyticThe sample is 198 active students in semester 1, 3 and 5. The sampling technique is Stratified Random Sampling using the sample size calculator. Univariate analysis using one sample t-test, one way anova and independent sample test. The results showed that the percentage level of knowledge of the Medical Study Program students at the University of Tanjungpura on the use of generic drugs was sufficient (64.88%). In conclusion, there is no significant difference between knowledge by gender, age and semester level so it is not a factor that affects a person's level of knowledge.